Can models of distributed leadership be used to mobilise networked generated innovation in schools? A case study from England. (August 2020) - Brown, Chris; MacGregor, Stephen; Flood, Jane
Abstract: There is now an increased focus on using networks to drive school improvement. Achieving the benefits of engaging in networks requires leaders to think and act differently; specifically, to benefit all teachers and students, the leaders of schools participating in networks must actively support the mobilization of networked-driven innovations. One approach to mobilization is enabling distributed leadership-type approaches. At the same time, distributed leadership, as a means of facilitating the take-up of network-led innovation, is relatively understudied. This paper explores how distributed leadership approaches can support innovation mobilization (or not) and what is required for them to do so effectively.